1998
DOI: 10.1021/jp973134g
|View full text |Cite
|
Sign up to set email alerts
|

Electronic, Structural, and Reactive Properties of Ultrathin Aluminum Oxide Films on Pt(111)

Abstract: Low-energy electron diffraction, X-ray photoelectron spectroscopy, high-resolution electron energy-loss spectroscopy, scanning tunneling microscopy, and temperature-programmed reaction spectrometry results are reported for the structural and reactive behavior of alumina films grown on Pt(111) as a function of thickness and oxidation temperature. Submonolayer Al films undergo compete oxidation at 300 K, annealing at 1100 K resulting in formation of somewhat distorted crystalline γ-alumina. Thicker deposits requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…In addition, the formation of an aluminium sulfate phase is thought to activate dissociative chemisorption of propane which enhances the ease of oxidation suggesting that sulfur may have more than one function (i.e., modifying the active metal and the support). 95 The belief that sulfur modifies both the metal and support contrasts with other literature where only the support and metal-support interface are thought to be modified. [89][90][91] In addition to the use of propane to represent hydrocarbon automotive exhausts, methane is also known to be present, and in fact, the added challenge of removing this from vehicle exhausts has, since 2009, led to a new emission standard described as non-methane hydrocarbons (NMHC).…”
Section: The Influence Of Sulfur On Hydrocarbon Oxidationmentioning
confidence: 92%
“…In addition, the formation of an aluminium sulfate phase is thought to activate dissociative chemisorption of propane which enhances the ease of oxidation suggesting that sulfur may have more than one function (i.e., modifying the active metal and the support). 95 The belief that sulfur modifies both the metal and support contrasts with other literature where only the support and metal-support interface are thought to be modified. [89][90][91] In addition to the use of propane to represent hydrocarbon automotive exhausts, methane is also known to be present, and in fact, the added challenge of removing this from vehicle exhausts has, since 2009, led to a new emission standard described as non-methane hydrocarbons (NMHC).…”
Section: The Influence Of Sulfur On Hydrocarbon Oxidationmentioning
confidence: 92%
“…To fabricate these devices, one requires the control of the growth modes adopted by thin films deposited on a substrate. [1][2][3][4][5][6][7][8][9][10][11] It is quite remarkable that the substrate plays an important role in the electronic properties of metallic adlayers where the interactions with the substrate material are crucial. [1][2][3][4][5] This can provide valuable information about the growth modes of thin films and intermixing phenomena at the interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the properties of low dimensional systems, e.g., ultrathin films and surface alloys, can be quite different from their bulk properties. [6][7][8][9][10][11] It was shown that the metals deposited on substrate can occupy the topmost surface sites, diffuse into the subsurface, and alloy formation occurs at the intermixed regime of bimetallic surfaces. 12 The migration of Al atoms and formation of complex surface alloy phases were observed by using scanning tunneling microscopy (STM).…”
Section: Introductionmentioning
confidence: 99%
“…One such example is the growth of FeO on Pt͑111͒. [10][11][12][13][14] Some of these novel materials exhibit unique electronic 15,16 and/or ferromagnetic properties. 17 Furthermore, bulk oxides often lack stable polar surfaces, but these surfaces may also be stabilized on ultrathin films.…”
Section: Introductionmentioning
confidence: 99%